Modeling the Pathways and Accumulation Patterns of Micro- and Macro-Plastics in the Mediterranean - Tsiaras, Kostas; Hatzonikolakis, Yannis; Kalaroni, Sofia; Pollani, Annika; Triantafyllou, George (Frontiers in Marine Science, 2021)
The Mediterranean is considered a hot-spot for plastic pollution, due to its semi-enclosed nature and heavily populated coastal areas. In the present study, a basin-scale coupled hydrodynamic/particle drift model was used to track the pathways and fate of plastics from major land-based sources (coastal cities and rivers), taking into account of the most important processes (advection, stokes drift, vertical and horizontal mixing, sinking, wind drag, and beaching). A hybrid ensemble Kalman filter algorithm was implemented to correct the near- surface circulation, assimilating satellite data (sea surface height, temperature) in the hydrodynamic model. Different size classes and/or types of both micro- and macroplastics were considered in the model. Biofouling induced sinking was explicitly described, as a possible mechanism of microplastics removal from the surface. A simplified parameterization of size-dependent biofilm growth has been adopted, as a function of bacterial biomass (obtained from a biogeochemical model simulation), being considered a proxy for the biofouling community. The simulated distributions for micro- and macroplastics were validated against available observations, showing reasonable agreement, both in terms of magnitude and horizontal variability. An 8-year simulation was used to identify micro- and macroplastics accumulation patterns in the surface layer, water column, seafloor and beaches. The impact of different processes (vertical mixing, biofouling, and wind/wave drift) was identified through a series of sensitivity experiments. For both micro- and macroplastics, distributions at sea surface were closely related to the adopted sources. The microplastics concentration was drastically reduced away from source areas, due to biofouling induced sinking, with their size distribution dominated by larger (>1 mm) size classes in open sea areas, in agreement with observations. High concentration patches of floating plastics were simulated in convergence areas, characterized by anticyclonic circulation. The distribution of macroplastics on beaches followed the predominant southeastward wind/wave direction. In the water column, a sub-surface maximum in microplastics abundance was simulated, with increasing contribution of smaller particles in deeper layers. Accumulation of microplastics on the seafloor was limited in relatively shallow areas (<500 m), with bottom depth below their relaxation depth due to defouling. The simulated total amount of floating plastics (∼3,760 tonnes) is comparable with estimates from observations.